Spectroscopic Studies of Soft X-Ray Emission from Gadolinium Plasmas - I Kambali; G. OSullivan (PPIKSN-BATAN, 2014)
The temporal behavior of gadolinium (Gd) laser-produced plasmas has been studied using a modified grazing incidence spectrometer which allows to capture the evolution of the plasma with spectral and temporal resolution of 0.1 nm and 1 ns, respectively. Experimental results indicate that the soft X-ray emission follows the temporal behavior of the laser pulse at high laser power density of Ф = 4.4×1012 W/cm2 in which the soft X-ray emission lasts for 7.5 ns (at FWHM) whereas at Ф = 5.4×1011 W/cm2 and Ф = 7.6×1010 W/cm2 the emission lasts for only 4 ns and 2.5 ns respectively,these are shorter than laser pulse duration due to lower electron temperatures achieved in the plasma generation. Lower Gd ion stages ranging from Gd11+ – Gd14+ are also found to contribute to the spectral emission over time.Received: 08 November 2013; Revised: 09 May 2014; Accepted: 09 May 2014